Ignacio de Assis Silva e os estudos literários - Leonel, Maria Celia de Moraes [UNESP] (My University, 2010)
This paper aims to honor the semiotician Ignacio Assis Silva printed by the intensity in all his activities, emphasizing mainly on the accuracy insightful essays, which made him not only one of the most important promoters of semiotics greimasian in Brazil, but one of those responsible for its development. It should be noted also that he served with dedication in the Postgraduate Program in Literary Studies FCL/Araraquara UNESP, including efforts since its founding. The program owes much to him and others of FCL semioticians for the healthy integration between programs, Linguistics/Portuguese Language and Literary Studies. The latter was even initially, a literature program focusing on semiotics greimasian. Join together with all his persistent interest in building a "theory of language", which deeply and tenaciously pursued in their classes and in their texts and can be detected in Figurativização e metamorfose: o mito de Narciso (1995).

O texto pretende homenagear o semioticista Ignacio Assis Silva pela intensidade impressa em suas atividades de toda ordem. Destaque-se, principalmente, o rigor nos ensaios percucientes, tendo sido não apenas um dos mais importantes divulgadores da semiótica greimasiana no Brasil, mas também um dos responsáveis por seu desenvolvimento. Ressalte-se ainda a dedicação com que atuou no Programa de Pós-Graduação em Estudos Literários da FCL/UNESP de Araraquara, envidando esforços na sua fundação. Deve-se muito aos semioticistas a saudável integração entre o Programa de Linguística e Língua Portuguesa e o de Estudos Literários, inicialmente um programa de literatura centrado na semiótica. Alie-se a isso o persistente interesse do Ignacio pela construção de uma “teoria sobre a linguagem”, que perseguiu profunda e tenazmente em suas aulas e em seus textos e que pode ser detectada em Figurativização e metamorfose: o mito de Narciso (1995).
Ignacio Assis Silva and literary studies
Keywords: Ignacio Assis Silva; Semiotics; Postgraduate Program in Literary Studies; Theory of Language; Ignacio Assis Silva; Semiótica; Programa de Pós-Graduação em Estudos Literários; Teoria da Linguagem